ANALISIS INVESTASI DAN ASURANSI PADA TUAN HANS HIGH NET WORTH INDIVIDUAL - , Fachri Wardian Fachril ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This thesis is how to manage the wealth of high net worth individual, Hans. This thesis discusses the profile of client by type of risk taking, evaluating and investment protection in the allocation of property assets, to evaluate the transition of wealth and formulate alternative solution to problems for Hans based on pillars contained in the Wealth Management. Client in this thesis is aged 45 years and works asa a dental conservation specialist, has two wives and two children. He does not have the health protection and protection of death so that the writing of this thesis focuses on how to evaluate and analyze protection for the welfare of Hans and his family with helath insurance and life insurance. Investment in financial instruments are only as a supplement in the writing of this, so that client can understand that investing in financial products more profitable and profide returns tha correspondend to be level of risk tolerance owned. The recomendations given is to do with the protection of health and life insurance, investment in financial instruments, pension funds prepared for Hans, and Hans's children's education savings.